Pineal region tumors: A diverse pathology in the seat of the soul - Jha, Rajiv; Tiwari, Jagannath (Journal of Society of Surgeons of Nepal, 2020)
Introduction: Pineal region tumors include a variety of neoplasms of different histological origin arising from the pineal gland itself and from structures of the parapineal area. It is a rare tumor which accounts for 0.4-1% of all intracranial tumors. The objective of this study was to describe the epidemiology, clinical presentation and histopathology of pineal region tumors at National Neurosurgical Referral Center, Nepal. Methods: This was a descriptive study of all cases of pineal region tumors which were operated between January 2013 and December 2019 at National Neurosurgical Referral Center, National Academy of Medical Sciences, Bir Hospital. Results: A total of 14 cases were operated during the study period. The mean age was 12 years (4-50 years) with male preponderance (64%). Most of these patients had clinical features of raised intracranial pressure due to obstructive hydrocephalus followed by oculomotor sign in the form of Perinaud syndrome and endocrine dysfunction. Most common histopathology was Pineoblastoma in our study (4 out of 14). Conclusion: Pineal region tumors are most commonly seen in adolescent age group. Most common symptoms were features of raised intra cranial pressure due to hydrocephalus followed by Perinaud syndrome. Pineal region tumors consist of diverse histopathological variants.